Pembuatan Website Online Marketplace untuk PT. X - Rendy Cahyadi; Yulia -; Justinus Andjarwirawan (Jurnal Infra, 2015)
PT. X is a company which provides IT consultation, mobile software development, and website development. PT. X observing physical business transaction which have many problems, especially in terms of times and space. Improvement in technology can be allocated to ease business process which happens physically, to online. Although seems ease the transaction, there is still many problems occur in marketplace website such as reliability which makes the user refuse to transact online.The creation of marketplace website can be a solution to ease trading and information sharing. Websites marketplace that has been made also able to become the third party in transaction between buyers and sellers, in hopes of minimizing fraud. The making of marketplace will use the No-CMS framework because this framework have a content management system.The results obtained from the making of the application is considered to be quite good and in accordance with the requirements of PT. X. It can be concluded from the results of questionnaires to the owner of PT. X which gives very good overall score. On the user side, the website is also considered to be sufficient customer needs with a total score of 80% good and 20% very good on the questionnaire.